In the Figure below is shown the graph of this function. We have the following function:
![f(x)=x^3+2x^2-x-2](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E3%2B2x%5E2-x-2)
The
occurs when
, so:
![f(0)=(0)^3+2(0)^2-(0)-2=-2](https://tex.z-dn.net/?f=f%280%29%3D%280%29%5E3%2B2%280%29%5E2-%280%29-2%3D-2)
Therefore, the
is the given by the point:
![\boxed{(0,-2)}](https://tex.z-dn.net/?f=%20%5Cboxed%7B%280%2C-2%29%7D%20)
From the figure we have three
:
![\boxed{P_{1}(-2,0)} \\ \boxed{P_{2}(-1,0)} \\ \boxed{P_{3}(1,0)}](https://tex.z-dn.net/?f=%20%5Cboxed%7BP_%7B1%7D%28-2%2C0%29%7D%20%5C%5C%20%5Cboxed%7BP_%7B2%7D%28-1%2C0%29%7D%20%5C%5C%20%5Cboxed%7BP_%7B3%7D%281%2C0%29%7D%20)
So, the
occur when
. Thus, proving this:
![f(x)=x^3+2x^2-x-2 \\ \\ For \ P_{1}:\\ If \ x=-2, \ y=(-2)^3+2(-2)^2-(-2)-2=0 \\ \\ For \ P_{2}:\\ If \ x=-1, \ y=(-1)^3+2(-1)^2-(-1)-2=0 \\ \\ For \ P_{3}:\\ If \ x=1, \ y=(1)^3+2(1)^2-(1)-2=0](https://tex.z-dn.net/?f=%20f%28x%29%3Dx%5E3%2B2x%5E2-x-2%20%5C%5C%20%5C%5C%20For%20%5C%20P_%7B1%7D%3A%5C%5C%20If%20%5C%20x%3D-2%2C%20%5C%20y%3D%28-2%29%5E3%2B2%28-2%29%5E2-%28-2%29-2%3D0%20%5C%5C%20%5C%5C%20For%20%5C%20P_%7B2%7D%3A%5C%5C%20If%20%5C%20x%3D-1%2C%20%5C%20y%3D%28-1%29%5E3%2B2%28-1%29%5E2-%28-1%29-2%3D0%20%5C%5C%20%5C%5C%20For%20%5C%20P_%7B3%7D%3A%5C%5C%20If%20%5C%20x%3D1%2C%20%5C%20y%3D%281%29%5E3%2B2%281%29%5E2-%281%29-2%3D0%20)
Answer:
Step-by-step explanation:
X Y X Y
0 3 0 5
1 7 1 8
2 11 2 11
3 15 3 14
4 19 4 17
Answer:
ml hahhahahahahaha
Step-by-step explanation:
mlhahahahahahahaha
Answer:
![\displaystyle f'(x) = \bigg( \frac{1}{2\sqrt{x}} - \sqrt{x} \bigg)e^\big{-x}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%27%28x%29%20%3D%20%5Cbigg%28%20%5Cfrac%7B1%7D%7B2%5Csqrt%7Bx%7D%7D%20-%20%5Csqrt%7Bx%7D%20%5Cbigg%29e%5E%5Cbig%7B-x%7D)
General Formulas and Concepts:
<u>Algebra I</u>
Terms/Coefficients
<u>Calculus</u>
Differentiation
- Derivatives
- Derivative Notation
Basic Power Rule:
- f(x) = cxⁿ
- f’(x) = c·nxⁿ⁻¹
Derivative Rule [Quotient Rule]: ![\displaystyle \frac{d}{dx} [\frac{f(x)}{g(x)} ]=\frac{g(x)f'(x)-g'(x)f(x)}{g^2(x)}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7Bd%7D%7Bdx%7D%20%5B%5Cfrac%7Bf%28x%29%7D%7Bg%28x%29%7D%20%5D%3D%5Cfrac%7Bg%28x%29f%27%28x%29-g%27%28x%29f%28x%29%7D%7Bg%5E2%28x%29%7D)
Step-by-step explanation:
<u>Step 1: Define</u>
<em>Identify</em>
![\displaystyle f(x) = \frac{\sqrt{x}}{e^x}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%28x%29%20%3D%20%5Cfrac%7B%5Csqrt%7Bx%7D%7D%7Be%5Ex%7D)
<u>Step 2: Differentiate</u>
- Derivative Rule [Quotient Rule]:
![\displaystyle f'(x) = \frac{(\sqrt{x})'e^x - \sqrt{x}(e^x)'}{(e^x)^2}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%27%28x%29%20%3D%20%5Cfrac%7B%28%5Csqrt%7Bx%7D%29%27e%5Ex%20-%20%5Csqrt%7Bx%7D%28e%5Ex%29%27%7D%7B%28e%5Ex%29%5E2%7D)
- Basic Power Rule:
![\displaystyle f'(x) = \frac{\frac{e^x}{2\sqrt{x}} - \sqrt{x}(e^x)'}{(e^x)^2}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%27%28x%29%20%3D%20%5Cfrac%7B%5Cfrac%7Be%5Ex%7D%7B2%5Csqrt%7Bx%7D%7D%20-%20%5Csqrt%7Bx%7D%28e%5Ex%29%27%7D%7B%28e%5Ex%29%5E2%7D)
- Exponential Differentiation:
![\displaystyle f'(x) = \frac{\frac{e^x}{2\sqrt{x}} - \sqrt{x}e^x}{(e^x)^2}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%27%28x%29%20%3D%20%5Cfrac%7B%5Cfrac%7Be%5Ex%7D%7B2%5Csqrt%7Bx%7D%7D%20-%20%5Csqrt%7Bx%7De%5Ex%7D%7B%28e%5Ex%29%5E2%7D)
- Simplify:
![\displaystyle f'(x) = \frac{\frac{e^x}{2\sqrt{x}} - \sqrt{x}e^x}{e^{2x}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%27%28x%29%20%3D%20%5Cfrac%7B%5Cfrac%7Be%5Ex%7D%7B2%5Csqrt%7Bx%7D%7D%20-%20%5Csqrt%7Bx%7De%5Ex%7D%7Be%5E%7B2x%7D%7D)
- Rewrite:
![\displaystyle f'(x) = \bigg( \frac{e^x}{2\sqrt{x}} - \sqrt{x}e^x \bigg) e^{-2x}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%27%28x%29%20%3D%20%5Cbigg%28%20%5Cfrac%7Be%5Ex%7D%7B2%5Csqrt%7Bx%7D%7D%20-%20%5Csqrt%7Bx%7De%5Ex%20%5Cbigg%29%20e%5E%7B-2x%7D)
- Factor:
![\displaystyle f'(x) = \bigg( \frac{1}{2\sqrt{x}} - \sqrt{x} \bigg)e^\big{-x}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%27%28x%29%20%3D%20%5Cbigg%28%20%5Cfrac%7B1%7D%7B2%5Csqrt%7Bx%7D%7D%20-%20%5Csqrt%7Bx%7D%20%5Cbigg%29e%5E%5Cbig%7B-x%7D)
Topic: AP Calculus AB/BC (Calculus I/I + II)
Unit: Differentiation